PENTINGNYA KOMUNIKSI ORGANISASI, MOTIVASI KERJA DAN KOMPENSASI UNTUK MENINGKATKAN KINERJA GURU - Dedy Kusumah Wijaya; Anik Herminingsih (Universitas Jember, 2015)
The success of teachers in performing their duties also mean the institution's success in education. The purpose of this study was to determine the effect of organizational communication, work motivation, compensation on the performance of teachers. This research was explanatory quantitative research method using correlation and regression model. This research at SMA Yuppentek 1 Tangerang involved 69 teachers as respondents.The results showed that organizational communication, motivation and compensation partially and simultaneously have significant effects on the performance of teachers. This research supported the previos reseraches. Keywords: Organizational communication, work motivation, compensation, teacher performance.